Galantamine has impact on immunity in mice exposed to keyhole limpet hemocyanin - Pohanka, Miloslav; Zakova, Jitka; Fusek, Josef (My University, 2017)
OBJECTIVES: In this work, we hypothesized whether galantamine could interact with the cholinergic anti-inflammatory pathway and modulate immunity this way. BACKGROUND: Galantamine is a drug used for the therapy of Alzheimer disease. The drug inhibits enzyme acetylcholinesterase in the central nervous system, which causes better availability of neurotransmitter acetylcholine. METHODS: In the experiment, we immunized BALB/c laboratory mice by keyhole limpet hemocyanin (KLH) in combination with galantamine in a dose 0.02–0.5 mg/kg. The animals were sacrifi ced from 1 to 7 days after the substances applications and plasma was collected in order to examine immunochemical markers by enzymelinked immunosorbent assay. RESULTS: We found signifi cant drop in production of immunoglobulins and interleukin (IL) 4 level while IL2, IL4 and tumour necrosis factor α remained unaltered for the whole experiment. We infer that galantamine causes better availability of acetylcholine also in blood system, where the neurotransmitter interacts with nicotinic acetylcholine receptors on macrophages and initiates cholinergic anti-infl ammatory pathway. CONCLUSIONS: In a conclusion, galantamine can cause lower effi cacy of vaccination or immunity response to an infectious disease and the phenomenon should be taken into consideration in the current therapy.
Galantamin ovlivňuje imunitu u myší exponovaných klíčovým hemolymfatickým proteinem hemocyaminem
Keywords: acetylcholinesterase; alzheimer disease; cholinergic anti-infl ammatory pathway; galantamine; infl ammation; macrophage, inhibition.; Acetylcholinesteráza; Alzheimerova nemoc; cholinergní protizánětlivá dráha; galantamin; zánět; makrofág; inhibice.